Smart Operation for Power Distribution Systems Concepts and Applications (Springer International Publishing, 2018)
This book discusses the operation of electrical distribution systems, presenting contemporary concepts and applications with a focus on integration for smart operation and grids. The authors address the main concepts and techniques of active management of smart electrical distribution system operation, including state estimation, self healing, volt-var control, protection systems, operations planning, and commercial and emergency dispatch. From each topic, an overview of concepts are given together with examples related to the management of these systems, thus providing a valuable resource for the design, implementation and management of efficient and truly sustainable smart systems.